EXPERIMENTAL STUDIES OFFERROCEMENT COVERING ELEMENTS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The sequence and the requirements are described for designing of reinforcing cages and the structure of concrete for slabs. The placement of strain gauges on the slab and the process of the experiment are provided. The results of the experimental studies of the ferroconcrete covering elements are showed and the dependence of deformation on load is plotted. Keywords:ferrocement, structural construction, guy rope, shell.